Integrating a STEAM-Based Learning Model with Maja Labo Dahu Local Wisdom to Enhance Creativity and Character Development in Early Childhood - I'in Anggryani; Candra Kartikasari; Riqqo Tulqulub; Mahrati Imaniar; Najamuddin; Roswati; Muh Rusdi (CV. Creative Tugu Pena, 2025)
Early Childhood Education (ECE) plays a fundamental role in shaping children’s cognitive, social, emotional, and moral capacities, yet many learning models still separate the development of creativity from character formation. This paper examines the integration of the STEAM learning model with the local wisdom of Maja Labo Dahu from the Dana Mbojo community as an innovative and culturally relevant approach to early childhood education. The study aims to analyze how STEAM, with its emphasis on exploration, creativity, and problem-solving, can be aligned with values of honesty, responsibility, respect, and constructive self-awareness embodied in Maja Labo Dahu, and how this integration contributes to children’s creativity and character development. Using a qualitative descriptive library research method, the study systematically reviews journal articles, books, research reports, and official documents selected purposively based on relevance and academic credibility. Data were analyzed through content analysis to synthesize conceptual linkages among STEAM, cultural values, creativity, and character. The findings indicate that the integration of STEAM with Maja Labo Dahu creates a holistic learning environment that enhances children’s creative thinking while grounding their actions in ethical and culturally meaningful values. STEAM activities become more contextual when infused with cultural narratives, modeling, habituation, and collaborative learning that reinforce moral awareness and social competence. The study concludes that this integrative model is highly relevant for Indonesian early childhood education, as it bridges global competencies with local cultural identity, enriches pedagogical practices, and provides a theoretical contribution to culturally responsive and ethnopedagogical learning frameworks